The human fungal pathogen Paracoccidioides brasiliensis ( Onygenales : Ajellomycetaceae ) is a complex of two species : phylogenetic evidence from five mitochondrial markers (2010)
ABSTRACT: Paracoccidioides brasiliensis is the aetiological agent of paracoccidioidomycosis, the most important systemic mycosis in Latin America. In order to study the diversity of P. brasiliensis mitochondrial genes, to evaluate previous taxonomic proposals, and to explore the hypothesis that the previously described ‘‘divergent isolate’’ B30 (also called Pb01) could represent a new P. brasiliensis species, we undertook a molecular phylogenetic analysis based on five mitochondrial markers. Mitochondrial sequences of 59 P. brasiliensis isolates obtained from clinical and environmental samples, and the orthologous genes from outgroup species, are reported and analysed using parsimony and Bayesian methods. The combined data set comprised 2364 characters, of which 426 were informative. One of the studied strains presented a 376-nt insertion at the apocytochrome b (cob) gene. The corresponding sequence had a high similarity (79%) with an intron found in the Neurospora crassa cob gene. Interestingly, this intron is absent in the previously published sequence of the P. brasiliensis mitochondrial genome. Our trees were moderately congruent with the previous P. brasiliensis taxonomic proposals. Furthermore, we identified a new monophyletic group of strains within P. brasiliensis. Nevertheless, the phylogenetic species recognition (PSR) analyses described here suggested that these groups of strains could represent geographical variants rather than different Paracoccidioides cryptic species. In addition, and as previously proposed by other authors, these analyses supported the existence of a new specie of Paracoccidioides, which includes the previously described, divergent isolate B30 ⁄Pb01. This is the first report providing evidence, independent of nuclear markers, for the split of this important human pathogen into two species. We support the formal description of the B30 ⁄Pb01 as new specie.